2017
DOI: 10.1249/mss.0000000000001373
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Men, 3510 Marathons, Cardiac Risk Factors, and Coronary Artery Calcium Scores

Abstract: Among experienced males who have run marathons for 26-34 yr and completed between 27 and 171 marathons, CAC score is related to CAD risk factors and not the number of marathons run or years of running. This suggests that among long-term marathoners, more endurance exercise is not associated with an increased risk of CAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…In a study conducted on marathon runners who have run at least one marathon per year for 25 years, an increase in coronary artery calcification was noted, however it appeared to be related to the presence of cardiovascular risk factors and not to the number of marathons or training years [116]. Two other studies investigating the correlation between high exercise levels and coronary calcification have found a higher presence of atherosclerotic plaques in highly trained subjects compared to sedentary ones, however, these have better stability and a more favorable composition for the same cardiovascular risk profile [117,118].…”
Section: Exercise Dose and Adverse Effectsmentioning
confidence: 96%
“…In a study conducted on marathon runners who have run at least one marathon per year for 25 years, an increase in coronary artery calcification was noted, however it appeared to be related to the presence of cardiovascular risk factors and not to the number of marathons or training years [116]. Two other studies investigating the correlation between high exercise levels and coronary calcification have found a higher presence of atherosclerotic plaques in highly trained subjects compared to sedentary ones, however, these have better stability and a more favorable composition for the same cardiovascular risk profile [117,118].…”
Section: Exercise Dose and Adverse Effectsmentioning
confidence: 96%
“…Studies in endurance runners show that the frequency of adverse cardiovascular events in marathoners is equivalent to that in a population with established CHD, suggesting that too much exercise may be detrimental ( 132 ). An upper limit for the cardiovascular benefits of exercise is further supported by a recent study showing that individuals who completed at least 25 marathons over a period of 25 years have higher than expected levels of coronary artery calcification (CAC) and calcified coronary plaque volume when compared with sedentary individuals ( 133 ). A recent investigation also showed that individuals who maintain very high levels of physical activity (~3 times recommended levels) have higher odds of developing CAC, particularly in white males ( 134 ).…”
Section: Concluding Remarks and Remaining Questions To Be Addressedmentioning
confidence: 99%
“…While too much exercise may be detrimental and is associated with increased risk of cardiovascular mortality [47,75]. Reports in endurance runners demonstrated that marathoners who completed at least 25 marathons in more than 25 years normally possess more severe coronary artery calcification and calcified coronary plaque [78]. A recent survey denoted that individuals who maintain a very high level of physical activity have likely higher odds of developing coronary artery calcification, especially in white American males [79].…”
Section: Risk Of Exercise For Cardiovascular Functionmentioning
confidence: 99%